A cross-sectional study to assess knowledge of women about cervical cancer: an urban and rural comparison - Małgorzata Lesińska-Sawicka (Komiyama Printing Co. Ltd, 2021)
Abstract Introduction Cervical cancer and its etiopathogenesis, the age of women in whom it is diagnosed, average life expectancy, and prognosis are information widely covered in scientific reports. However, there is no coherent information regarding which regions-urban or rural-it may occur more often. This is important because the literature on the subject reports that people living in rural areas have a worse prognosis when it comes to detection, treatment, and life expectancy than city dwellers. Material and methods The subjects of the study were women and their knowledge about cervical cancer. The research was carried out using a survey directly distributed among respondents and via the Internet, portals, and discussion groups for women from Poland. Three hundred twenty-nine women took part in the study, including 164 from rural and 165 from urban areas. The collected data enabled the following: (1) an analysis of the studied groups, (2) assessment of the respondents' knowledge about cervical cancer, and (3) comparison of women's knowledge depending on where they live. Results The average assessment of all respondents' knowledge was 3.59, with women living in rural areas scoring 3.18 and respondents from the city-4.01. Statistical significance (p < 0.001) between the level of knowledge and place of residence was determined. The results indicate that an increase in the level of education in the subjects significantly increases the chance of getting the correct answer. In the case of age analysis, the coefficients indicate a decrease in the chance of obtaining the correct answer in older subjects despite the fact that a statistically significant level was reached in individual questions. Conclusions Women living in rural areas have less knowledge of cervical cancer than female respondents from the city. There is a need for more awareness campaigns to provide comprehensive information about cervical cancer to women in rural areas. A holistic approach to the presented issue can solve existing difficulties and barriers to maintaining health regardless of the place of life and residence. Implication for cancer survivors They need intensive care for women's groups most burdened with risk factors.